Immunological signatures unveiled by integrative systems vaccinology characterization of dengue vaccination trials and natural infection - Plaça, Desirée Rodrigues; Fonseca, Dennyson Leandro M.; Marques, Alexandre H. C.; Zaki Pour, Shahab; Usuda, Júlia Nakanishi; Baiocchi, Gabriela Crispim; Prado, Caroline Aliane de Souza; Salgado, Ranieri Coelho; Filgueiras, Igor Salerno; Freire, Paula Paccielli; Rocha, Vanderson; Camara, Niels Olsen Saraiva; et al. (Frontiers in Immunology, 2024)
Dengue virus (DENV) infection is a global health problem lacking specific therapy, requiring an improved understanding of DENV immunity and vaccine responses. Considering the recent emerging of new dengue vaccines, here we performed an integrative systems vaccinology characterization of molecular signatures triggered by the natural DENV infection (NDI) and attenuated dengue virus infection models. We analyzed 955 samples of transcriptomic datasets of patients with NDI and attenuated dengue virus infection trials (DVT1, DVT2, and DVT3). Differential expression analysis identified 237 common differentially expressed genes (DEGs) between DVTs and NDI. Among them, 28 and 60 DEGs were up or downregulated by dengue vaccination during DVT2 and DVT3, respectively, with 20 DEGs intersecting across all three DVTs. Enriched biological processes of these genes included type I/II interferon signaling, cytokine regulation, apoptosis, and T-cell differentiation. Principal component analysis based on 20 common DEGs (overlapping between DVTs and our NDI validation dataset) distinguished dengue patients by disease severity, particularly in the late acute phase. Machine learning analysis ranked the ten most critical predictors of disease severity in NDI, crucial for the anti-viral immune response. This work provides insights into the NDI and vaccine-induced overlapping immune response and suggests molecular markers (e.g., IFIT5, ISG15, and HERC5) for anti-denguespecific therapies and effective vaccination development.